Lipid Formulations of Amphotericin B Significantly Improve Outcome in Solid Organ Transplant Recipients with Central Nervous System Cryptococcosis - Sun, Hsin-Yun (2009)
BACKGROUND: Whether outcome of central nervous system (CNS) cryptococcosis in solid organ transplant (SOT) recipients treated with lipid formulations of amphotericin B is different from that with amphotericin B deoxycholate (AmBd) is not known. METHODS: A cohort comprising consecutive SOT recipients with CNS cryptococcosis in a multicenter study. RESULTS: Of 75 patients treated with the polyenes as induction regimens, 55 (73.3%) received lipid formulations of amphotericin B and 20 (26.7%) received AmBd. Similar proportions of patients in two groups had renal failure at baseline (p=0.94). Overall mortality at 90 days was 10.9% in the lipid formulations of amphotericin B and 40.0% in the AmBd group. In univariate analysis, non-receipt of calcineurin inhibitors (p=0.034), renal failure at baseline (p=0.016) and fungemia (p=0.003) were significantly associated with mortality. Compared with AmBd, lipid formulations of amphotericin B were associated with a lower mortality (p=0.007). Mortality did not differ in patients receiving lipid formulations of amphotericin B with or without flucytosine (p=0.349). In stepwise logistic regression analysis, renal failure at baseline [odds ratio (OR) 4.61, 95% confidence interval (CI) 1.02-20.80, p=0.047] and fungemia (OR 10.66, 95% CI 2.08-54.55, p=0.004) were associated with an increased mortality while lipid formulations of amphotericin B were associated with a lower mortality (OR 0.11, 95% CI 0.02-0.57, p=0.008). CONCLUSION: Lipid formulations of amphotericin B were independently associated with better outcome and may be considered the first-line treatment for CNS cryptococcosis in these patients.